(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the main principles of TBA, its role and advantages in the learning process. It also discusses methods for developing students’ linguistic and communicative skills through tasks based on real-life situations. The effectiveness of TBA is illustrated through practical examples such as creating a tourist guide, organizing debates on social problems, and analyzing the media. The main advantages of the method are emphasized as learning the language in a natural environment, developing students’ independent and creative thinking skills, and forming teamwork skills.